2016
DOI: 10.3390/dj4030031
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Vertical Fit along the Implant-Abutment Interface: A Microscope Qualitative Analysis

Abstract: The aim of this study was to qualitatively evaluate the marginal vertical fit along two different implant-abutment interfaces: (1) a standard abutment on an implant and (2) a computer-aided-design/computer-aided-machine (CAD/CAM) customized screw-retained crown on an implant. Four groups were compared: three customized screw-retained crowns with three different “tolerance” values (CAD-CAM 0, CAD-CAM +1, CAD-CAM −1) and a standard titanium abutment. Qualitative analysis was carried out using an optical microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…Since some degrees of error and deformity are inevitable in both techniques, attempts must be made to minimize distortion during different phases of impression making as well as during the transfer of the implant position to the final cast in order to fabricate stress-free implant-supported restorations. 21,22 Carr found no significant difference between the openand closed-tray impression techniques when making the impressions of 2 implants with 15° divergence. 17 Conrad et al evaluated 3 implants and reported a similar level of distortion and deformity for the 2 impression techniques.…”
Section: Discussionmentioning
confidence: 94%
“…Since some degrees of error and deformity are inevitable in both techniques, attempts must be made to minimize distortion during different phases of impression making as well as during the transfer of the implant position to the final cast in order to fabricate stress-free implant-supported restorations. 21,22 Carr found no significant difference between the openand closed-tray impression techniques when making the impressions of 2 implants with 15° divergence. 17 Conrad et al evaluated 3 implants and reported a similar level of distortion and deformity for the 2 impression techniques.…”
Section: Discussionmentioning
confidence: 94%
“…The amount of these micro gaps and their clinical signi cance have been getting remarkable attention. (4,7,27,28) Accordingly, different proposed methods have been employed to measure those micro gaps including the use of direct visualization under optical microscope (29) , or traveling microscope (28) microtomography, (30) and the analyzing method under scanning electron microscopy (SEM), (31) for either sectioned or embedded specimens and the use of a silicone replica. Although these techniques are well recognized, nevertheless, it is impossible to be used in vivo and several authors agreed that these measurements could involve unavoidable human errors, along with the non-standardized evaluation areas.…”
Section: Discussionmentioning
confidence: 99%
“…These factors could be the alteration in the radius of the instruments during the milling procedure, the wear of the milling tools and the size of the milling drills. (42) Mobilio et al (29) reported that the tolerance set for fabrication of either screw retained abutments or crowns during CAD/CAM procedure could have a major role in their nal t to implant. The study claimed that reduction in tolerance values by 10-µm could increase the attrition and, subsequently, the vertical t between the components.…”
Section: Discussionmentioning
confidence: 99%
“…Outro adendo concerne ao equipamento empregado na avaliação. Nesta pesquisa, preferiu-se operar o microscópio eletrônico de varredura (MEV), em detrimento do microscópio óptico (Mobilio et al, 2016;Rodrigues et al, 2017).…”
Section: Gruposunclassified